Mobile and Ubiquitous Learning An International Handbook - Yu, Shengquan; Ally, Mohamed; Tsinakos, Avgoustos (Perspectives on Rethinking and Reforming Education, 2018)
XIV, 377 p. 62 illus., 48 illus. in color.